Surveillance of psychomotor development and alarm signals (Portuguese Journal of Family Medicine and General Practice, 2009)
Over the last few decades, there has been a growing interest in pediatric developmental problems, their early diagnosis and intervention.The advances in therapeutics and preventive medicine in other fields opened the way for development to emerge as a new challenge for doctors. This paper will review the importance of developmental surveillance within the pediatric clinical setting and the warning signs that should alert doctors to act timely to prevent or minimize disease progression.Although not exhaustive, this review article intends to give practical solutions to clinicians
Keywords: Child Development; Signs; Prevention; Surveillance